Mobile Simulation Circular Angle Cutting Product for Tooling on Welding Application - Rozali, Mohd Zulfadli; Supidin, Izzat Fahmi Mohamad (Research and Innovation in Technical and Vocational Education and Training, 2021)
The quality of finishing that is not uniform in machine use is a source of problems and often occurs when making cutting-edge designs. Therefore, a study was developed to invent a Mobile Circular Angle Cutting Machine that can be used for the circle cutting process for a circle-shaped design. The development of this mobile circle cutting machine utilizes the ADDIE model consisting of 5 stages used in the development of this product which were, the process of interviewing, gathering information, analyzing data, product design, implementation and evaluation. This mobile circle cutting machine could not be developed in the exact form as described in the study limitations. However, it was developed by using inventory software to simulate the machine. This cutting process uses a machine grinder which is a key tool in iron cutting. This cutting process can provide finesse and uniformity of the cutting result and can also save time. This round angle cutting machine is only capable of cutting cuts of 0.5 mm, 0.8 mm and 1.2 mm thick metal pieces to avoid damage to the grinder machine points used on the round corner cutting machines. The researcher also obtained endorsement from three experts in engineering, industrial design and welding. The results from the simulations developed show that all experts have agreed that this product will work well and can be developed for the purpose of rounding the corners. However, this portable cutting machine still has room for improvement in the metal manufacturing industry.